Finding options beyond standard of care in oncology: a proposal for workflows utilizing knowledge databases - Glocker, Katrin; Ahlbrandt, Janko; Knurr, Alexander; Horak, Peter; Heining, Christoph; Ückert, Frank (MEDINFO 2019, 2019)
With the novel approach of molecularly stratified therapies based on genetic characteristics of individual tumors, the need for databases providing information on molecular alterations and targeted treatment options is increasing rapidly. In Molecular Tumor Boards (MTB) professionals discuss molecular alterations and provide biological context for therapeutic options using external knowledge databases. The identification of informative databases and the information on their specific contents can greatly facilitate and standardize the functioning of a MTB. In this work we present a list of databases which have been deemed useful and relevant for MTB in a clinical setting. We describe workflows to recommend the use of specific databases at different steps in the clinical curation process. Information obtained from these databases is a necessary prerequisite to evaluate molecular alterations and devise rational targeted therapies in MTB.